2020
DOI: 10.1159/000512178
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Xanthine Oxidase Inhibitors in Hyperuricemic Patients

Abstract: This review aim is to critically resume the available clinical evidence supporting the treatment of chronic hyperuricemia with xanthine-oxidase inhibitor activity. For this reason, all of the studies published in English language from 2000 to August 2019 on uric acid-lowering drugs have been carefully reviewed. The terms “serum uric acid”, “xanthine oxidase”, “allopurinol”, “febuxostat”, and “topiroxostat” have been incorporated into an electronic search strategy, alone and in combinations, in both MEDLINE (Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 75 publications
(84 reference statements)
1
41
0
4
Order By: Relevance
“…Additionally, aldehyde dehydrogenase II (ALDH-2) polymorphisms have been associated with SUA levels and hypertension in genome wide association studies [ 86 ]. Other genetic polymorphisms that regulate SUA levels and associate with hypertension are XOR gene variants [ 85 , 87 , 88 ]. Of note, XOR is not only associated with increased SUA levels, but also with increased oxidative stress, which in turn may lead to the development of hypertension [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, aldehyde dehydrogenase II (ALDH-2) polymorphisms have been associated with SUA levels and hypertension in genome wide association studies [ 86 ]. Other genetic polymorphisms that regulate SUA levels and associate with hypertension are XOR gene variants [ 85 , 87 , 88 ]. Of note, XOR is not only associated with increased SUA levels, but also with increased oxidative stress, which in turn may lead to the development of hypertension [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other genetic polymorphisms that regulate SUA levels and associate with hypertension are XOR gene variants [ 85 , 87 , 88 ]. Of note, XOR is not only associated with increased SUA levels, but also with increased oxidative stress, which in turn may lead to the development of hypertension [ 87 , 88 ]. In contrast with the aforementioned studies, the genetic risk score developed using 30 gene variants responsible for SUA levels has been associated with lower BP values [ 84 ].…”
Section: Discussionmentioning
confidence: 99%
“…Xanthine oxidase [XO] is the form of enzyme xanthine dehydrogenase responsible for converting hypoxanthine to UA in the purine metabolism pathway. During this process, there is the production of reactive oxygen species [ROS] [ 15 ]. When produced in excess, ROS reduces the synthesis of nitric oxide and lead to endothelial dysfunction [ 15 ].…”
Section: Drugs Reducing the Generation Of Uric Acid: The Xanthinementioning
confidence: 99%
“…During this process, there is the production of reactive oxygen species [ROS] [ 15 ]. When produced in excess, ROS reduces the synthesis of nitric oxide and lead to endothelial dysfunction [ 15 ]. A meta-analysis pooling data from 81 randomized clinical trials (RCTs) (N. 10684 included patients) showed that the xanthine oxidase inhibitors [XOIs] decreases the risk of total and serious cardiovascular events [Odds Ratio—OR = 0.60, p = 0.001 and OR = 0.64, p < 0.01 respectively] and onset/worsening hypertension [OR = 0.54, p = 0.002] in comparison with placebo.…”
Section: Drugs Reducing the Generation Of Uric Acid: The Xanthinementioning
confidence: 99%
“…The increased serum UA level has a similar prognostic impact in CVE and all-cause mortality, whether caused by increased generation or reduced excretion ( 12 ). Several studies have suggested that UA serves as an independent risk factor for CVD, that UA-lowering medicines improved cardiovascular outcomes, and that lowering the UA level is one of the most effective methods for reducing cardiovascular risk ( 1 , 13 ). However, both UA-lowering agents and very low levels of UA are threats to cardiovascular health.…”
Section: Discussionmentioning
confidence: 99%